Age‐ and sex‐specific morphologic changes in the metaphyseal fossa adjacent to epiphyseal tubercle in children and adolescents without hip disorders. Issue 10 (3rd March 2020) - Hosseinzadeh, Shayan; Novais, Eduardo N.; Maranho, Daniel A.; Emami, Seyed Alireza; Portilla, Gabriela; Kim, Young‐Jo; Kiapour, Ata M.
Abstract: The epiphyseal tubercle plays an important role in epiphyseal stabilization. While the majority of studies have focused on tubercle morphology, there is a paucity of information on the morphological features of the metaphyseal fossa, where the tubercle sits on the metaphysis. The goal of this study was to determine the developmental changes in the capital femoral metaphyseal fossa. Computed tomography of the pelvis from 80 children and adolescents 8‐15 years old were used to create three‐dimensional models of the proximal femur. Depth, width, length, and surface area of the metaphyseal fossa were measured and the impact of age and sex on fossa morphology was assessed using the linear regression and two‐way analysis of variance, respectively. The metaphyseal fossa was located in the posterosuperior quadrant of the metaphysis without any variations in the location with increasing age ( P > .1). However, with increasing age, there was a reduction in all metaphyseal fossa measurements including the depth, length, width, and surface area ( P < .01). No significant differences were noted for the metaphyseal fossa measurements between males and females ( P > .1). The metaphyseal fossa reduces in size from 8 to 15 years of age in a similar fashion in males and females. As the metaphyseal fossa adjacent to the tubercle matches the area where a focal radiolucency has been observed in early slipped capital femoral epiphysis (SCFE), further studies should clarify the mechanisms by which the interlocking interaction of the epiphyseal tubercle and its fossa contributes to or is affected by SCFE.